Economic growth - Barro, Robert J.; Sala-i-Martin, Xavier (Cambridge, Mass. : MIT Press, 2004)
This graduate level on economic growth surveys neoclassical and more recent growth theories, stressing their empirical implications and the relation of theory to data and evidence.
Includes bibliographical references (p. [627]-640) and index.
rua 22/05/13, uaj 10/06/13; oif 17/09/15
Loans
Keywords: Economic development -- Mathematical models